Pemberdayaan Jama’ah Masjid Melalui Program Pelatihan Hidroponik di Masjid Al-Kahfi Pandean - Nurul Akmalia Nurul; Wiji Indah Rahayu; Neli Elmaya Zakiyah (Ngabekti: Jurnal Pengabdian kepada Masyarakat, 2026)
This community assistance program focused on strengthening the internalization of adab (Islamic etiquette) among tahfidz students at Ribathul Qur’an wal Qira’at Islamic Boarding School, Malang, by cultivating sustainable habits within the halaqah learning environment. The program was designed to address practical challenges observed in daily activities, including punctuality, maintaining a conducive halaqah atmosphere, consistency in muraja’ah (Qur’anic revision), respect toward musyrif (supervisors), proper treatment of the mushaf and learning environment, and responsible smartphone use. A participatory assistance approach was employed, involving caregivers, musyrif, students, and student administrators through four stages: initial assessment, collaborative planning, intervention implementation, and continuous monitoring and reflection. The main interventions included the development of standard operating procedures (SOPs) for halaqah adab, micro-coaching sessions for musyrif, the establishment of peer mentors, the installation of visual reminders, and the use of simple monitoring instruments. The findings indicate gradual improvements in individual behavior, particularly in punctual attendance, readiness for Qur’anic recitation, and reduced digital distractions. At the social level, peer support strengthened positive social control while minimizing corrective practices that could cause embarrassment. At the institutional level, the implementation of SOPs and weekly evaluations promoted consistent standards across halaqah groups, making adab practices easier to sustain. This program recommends maintaining regular evaluation cycles, strengthening the peer mentoring system, and conducting continuous monitoring to ensure the long-term sustainability of behavioral improvements.